Hydrogen-rich syngas production by catalytic cracking of tar in wastewater under supercritical condition. (26th July 2019) - Yan, Mi; Liu, Jianyong; Hantoko, Dwi; Kanchanatip, Ekkachai; Grisdanurak, Nurak; Cai, Yi; Gao, Zengliang
Abstract: This paper presents the results from experimental study of syngas production by catalytic cracking of tar in wastewater under supercritical condition. Ni/Al2 O3 catalysts were prepared via the ultrasonic assisted incipient wetness impregnation on activated alumina, and calcined at 600 °C for 4 h. All catalysts showed mesoporous structure with specific surface area in a range of 146.6–215.3 m 2 /g. The effect of Ni loading (5–30 wt%), reaction temperature (400–500 °C), and tar concentration (0.5–7 wt%) were systematically investigated. The overall reaction efficiency and the gas yields, especially for H2, were significantly enhanced with an addition of Ni/Al2 O3 catalysts. With 20%Ni/Al2 O3, the H2 yield increased by 146% compared to the non-catalytic experiment. It is noteworthy that the reaction at 450 °C with the addition of 20%Ni/Al2 O3 had a comparable efficiency to the reaction without catalyst at 500 °C. The maximum H2 yield of 46.8 mol/kgtar was achieved with 20%Ni/Al2 O3 at 500 °C and 0.5 wt% tar concentration. The catalytic performance of the catalysts gradually decreased as the reuse cycle increased, and could be recovered to 88% of the fresh catalyst after regeneration. 20%Ni/Al2 O3 has a potential to improve H2 production, as well as a good reusability. Thus, it is considered a promising catalyst for energy conversion of tar in wastewater. Highlights: Catalytic conversion of tar to syngas in SCW (≥400 °C, >23 MPa) was investigated. Ni/Al2 O3 catalysts were prepared and they could be reused for more than 3 cycles. Gas yield at 450 °C with 20Ni/Al was comparable to that of 500 °C without catalyst. Highest H2 yield of 46.8 mol/kgtar was achieved with 20Ni/Al at 500 °C.